Kajian Literatur: Hubungan Self-Regulation dengan Children Well-Being pada Anak Usia Dini - Ayu Tasya Siti Fatimah; Taopik Rahman; Risbon Sianturi (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study examines the relationship between self-regulation and children’s well-being in early childhood through a literature review. Self-regulation is defined as the ability to manage emotions, thoughts, and behaviors to achieve goals, while children’s well-being refers to happiness, emotional stability, and life satisfaction. The findings indicate that strong self-regulation is associated with better emotional control, positive social interactions, and higher learning readiness. In contrast, low self-regulation is linked to behavioral problems and reduced well-being. Therefore, developing self-regulation from an early age is essential for supporting children’s overall development. The findings imply that early childhood educators and parents should integrate self-regulation training into daily learning activities, while policymakers may consider strengthening socio-emotional learning curricula in early childhood education settings